SPOTLIGHT on the Johannesburg Branch of the SAIMM - G. T. G. Emere (The Southern African Institute of Mining and Metallurgy, 1988)
The Johannesburg Branch of The South African Institute of Mining and Metallurgy was officially inaugurated at a General Meeting held in Kelvin House on Monday, 18th January, 1988. In addition to nominating committee members, Mr G. T.G. Emere delivered a presentation on the Barbrook gold-mining project, which is currently in the development phase some 40 km east of Barberton.